Combined effects of pollutants and salinity on embryo-larval development of the Pacific oyster, Crassostrea gigas. (February 2016) - Gamain, Perrine; Gonzalez, Patrice; Cachot, Jérôme; Pardon, Patrick; Tapie, Nathalie; Gourves, Pierre Yves; Budzinski, Hélène; Morin, Bénédicte
Abstract: For several years, low larval recruitment has been observed in Arcachon Bay, in southwest France. Exposure to pollutants could partly account for the reduction of early life stages of the Pacific oyster. This study evaluated the effects of copper and S-metolachlor in combination with salinity on the early life stages of Crassostrea gigas . Embryos were exposed to concentrations of copper (1, 10 and 50 μg L −1 ) or S-metolachlor (10, 100 and 1000 ng L −1 ) and six salinities (18, 21, 24, 27, 30 and 33 u.s.i). Embryotoxicity was measured by considering both the percentage of abnormalities and arrested development in D-shaped larvae. Embryo-larval development was only affected at salinities ≤24 u.s.i, which have never been observed during C. gigas reproduction period in Arcachon Bay. Both contaminants had an effect at environmental concentrations. Our results suggest that copper and metolachlor toxicity was enhanced with decreasing salinity. Highlights: Oyster embryos were exposed to copper, S-metolachlor and different salinities. Exposure to pollutants increase the percentage of larval abnormalities. Environmental concentrations of pesticides impair larvae-D development. Embryo-larval development is affected at salinities ≤24 u.s.i. Copper and metolachlor toxicity is enhanced with decreasing salinity.